Cervico-vaginal microflora in women in an ambulatory gynecology practice in Cali, Colombia (Colombia Medica, 1990)
Among attendants to a gynecological outpatient clinic of a health center in Cali, Colombia, 73 women of childbearing age were selected for a vaginal flora study. Vaginal discharges and cervix uteri specimens were taken to identify aerobic and anaerobic microorganisms. The presence of nitrites using reagent strips for urinalysis, as well as vaginal pH, were tested. Predominant bacteria isolated from the samples were Gardnerella vaginalis, 22.0%; Streptococcus, 20.0%; Staphylococcus, 17.8%; and Escherichia coli, 14.0%. Nitrites were more frequently positive in the presence of Streptococcus and E. coli, 73.3% and 60.0%, respectively. Vaginal pH between 5.0 and 6.0 was found in 78.0% of the women.